Protocol for the Development of Chinese Guideline for the Diagnosis and Management of Localized Scleroderma - WANG Zhaojian; MA Xuda; XIE Jiangmiao; ZOU Kun; LONG Xiao (Xiehe Yixue Zazhi)
Localized scleroderma (LoS) is a chronic autoimmune skin disorder characterized by fibrosis and hardening of the skin and subcutaneous tissues, potentially affecting deeper tissues and other organs. Currently, China lacks evidence-based guidelines for the diagnosis and management of LoS, which poses a challenge to disease recognition and leads to significant variation in treatment strategies across medical centers. To address this problem, we plan to establish a nationwide, multidisciplinary expert team through the Chinese Society of Plastic Surgery to initiate the development of the Chinese Guideline for the Diagnosis and Management of Localized Scleroderma. The guideline aims to standardize the diagnosis and treatment procedures for LoS, improve clinical diagnostic and therapeutic capabilities, and enhance patient outcomes through early identification and intervention. The guideline will adhere to international standards, with recommendations formed through evidence evaluation and multiple rounds of expert discussions. Although evidence-based data on LoS specific to the Chinese population is currently limited, and no unified gold standard for disease assessment exists, the clinical expertise of multidisciplinary specialists will play a pivotal role in the guideline's formulation. We anticipate that this guideline will provide LoS patients with higher-quality medical care and enhance patient awareness and engagement, which may ultimately help reduce social and healthcare burden. This proposal outlines the background, methodology, and anticipated value of the guideline, with the hope of providing guidance for its rigorous development and successful publication.